ErbB4 in the brain: Focus on high grade glioma - Pitcher, Jamie-Lee; Alexander, Naomi; Miranda, Panimaya Jeffreena; Johns, Terrance G. (Frontiers in Oncology, 2022)
The epidermal growth factor receptor (EGFR) family of receptor tyrosine kinases (RTKs) consists of EGFR, ErbB2, ErbB3, and ErbB4. These receptors play key roles in cell proliferation, angiogenesis, cell migration, and in some cases, tumor promotion. ErbB4 is a unique member of the EGFR family, implicated not only in pro-tumorigenic mechanisms, such as cell proliferation and migration, but also in anti-tumorigenic activities, including cell differentiation and apoptosis. ErbB4 is differentially expressed in a wide variety of tissues, and interestingly, as different isoforms that result in vastly different signalling outcomes. Most studies have either ignored the presence of these isoforms or used overexpression models that may mask the true function of ErbB4. ErbB4 is widely expressed throughout the body with significant expression in skeletal tissue, mammary glands, heart, and brain. Knockout models have demonstrated embryonic lethality due to disrupted heart and brain development. Despite high expression in the brain and a critical role in brain development, remarkably little is known about the potential signalling activity of ErbB4 in brain cancer. This review focuses on the unique biology of ErbB4 in the brain, and in particular, highlights brain cancer research findings. We end the review with a focus on high grade gliomas, primarily glioblastoma, a disease that has been shown to involve EGFR and its mutant forms. The role of the different ErbB4 isotypes in high grade gliomas is still unclear and future research will hopefully shed some light on this question.